New records of Milesina blechni and Milesina kriegeriana (Pucciniales) from the Ukrainian Carpathians - Tykhonenko, Yu.Ya.; Hayova, V.P. (Український ботанічний журнал, 2015)
Two species of Milesina (Pucciniales) collected in Gorgany Nature Reserve (Nadvirna District, Ivano- Frankivsk Region) in September 2014 are reported, M. blechni (Syd. et P. Syd.) Arthur ex Faull on Blechnum spicant (L.) Roth and M. kriegeriana (Magnus) Magnus on Dryopteris carthusiana (Vill.) H.P. Fuchs. These species have not been recorded in Ukraine for about a hundred years. Both rusts were found in very humid sites. Numerous observations of the same host plants under less humid conditions revealed no fungi. Descriptions, micrographs (SEM and LM) and distribution maps for the studied fungi are provided. Повідомляється про знахідки на території природного заповідника «Ґорґани» (Івано-Франківська область, Надвірнянський район) двох видів роду Milesina Magnus, які не реєструвалися в Україні вже протягом майже ста років: Milesina blechni (Syd. et P. Syd.) Arthur ex Faull на Blechnum spicant (L.) Roth і Milesina kriegeriana (Magnus) Magnus на Dryopteris carthusiana (Vill.) H.P. Fuchs. Обидва види знайдені в дуже вологих місцезнаходженнях. Ураження живильних рослин цих видів у сухіших оселищах не спостерігалось. Робота ілюстрована шістьма мікрофотографіями виявлених іржастих грибів і картами їх поширення. Сообщается о находках на территории природного заповедника «Горганы» (Ивано-Франковская область, Надворнянский район) двух видов рода Milesina Magnus, которые не регистрировались в Украине уже на протяжении почти столетия: Milesina blechni (Syd. et P. Syd.) Arthur ex Faull на Blechnum spicant (L.) Roth и Milesina kriegeriana (Magnus) Magnus на Dryopteris carthusiana (Vill.) H.P. Fuchs. Оба вида собраны в очень влажных местонахождениях. Развитие ржавчины на питающих растениях этих видов в более сухих биотопах не наблюдалось. Работа иллюстрирована шестью микрофотографиями обнаруженных ржавчинников и картами их распространения.